2016
DOI: 10.3390/nu8030133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trigonelline, an Alkaloid Present in Coffee, on Diabetes-Induced Disorders in the Rat Skeletal System

Abstract: Diabetes increases bone fracture risk. Trigonelline, an alkaloid with potential antidiabetic activity, is present in considerable amounts in coffee. The aim of the study was to investigate the effects of trigonelline on experimental diabetes-induced disorders in the rat skeletal system. Effects of trigonelline (50 mg/kg p.o. daily for four weeks) were investigated in three-month-old female Wistar rats, which, two weeks before the start of trigonelline administration, received streptozotocin (60 mg/kg i.p.) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 55 publications
4
22
0
1
Order By: Relevance
“…The serum level of fructosamine after six weeks was significantly increased in relation to the control rats ( Table 1 ). The body mass of the diabetic rats was lower than in the control healthy rats ( Figure 1 ), and the following osteoporotic changes developed in the skeletal system, as previously reported [ 43 ]: decreased bone mass and mineralization ( Figure 2 , Table 2 ), as well as decreased bone strength ( Table 3 ). The serum biochemical marker of bone formation (osteocalcin) was decreased and the marker of bone resorption (RatLaps) increased ( Table 1 ) in comparison with the healthy controls.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The serum level of fructosamine after six weeks was significantly increased in relation to the control rats ( Table 1 ). The body mass of the diabetic rats was lower than in the control healthy rats ( Figure 1 ), and the following osteoporotic changes developed in the skeletal system, as previously reported [ 43 ]: decreased bone mass and mineralization ( Figure 2 , Table 2 ), as well as decreased bone strength ( Table 3 ). The serum biochemical marker of bone formation (osteocalcin) was decreased and the marker of bone resorption (RatLaps) increased ( Table 1 ) in comparison with the healthy controls.…”
Section: Resultssupporting
confidence: 78%
“…The control rats (groups I, II and IV) received the vehicle (tap water) at the same volume of 2 mL/kg p.o. This study shared controls with our previous report [ 43 ]. The four-week period of caffeine administration was long enough to demonstrate effects of caffeine and other plant compounds on the skeletal system in rats [ 25 , 44 , 45 ].…”
Section: Methodsmentioning
confidence: 74%
“…Disorders such as DM affect all systems of the body (10, 11, 5360). For example, DM can negatively impact the immune system, musculoskeletal function, hepatic metabolism, and renal clearance (50, 53, 55, 59, 6164).…”
Section: Increased Lifespan Degenerative Disorders and Cell Injurymentioning
confidence: 99%
“…For example, DM can negatively impact the immune system, musculoskeletal function, hepatic metabolism, and renal clearance (50, 53, 55, 59, 6164). In the cardiovascular system, DM can lead to impaired angiogenesis, platelet dysfunction, atherosclerosis, endothelial progenitor cell injury, cardiac impairment, and loss of vascular cells (8, 14, 27, 62, 6568).…”
Section: Increased Lifespan Degenerative Disorders and Cell Injurymentioning
confidence: 99%
“…In another study on the effect of V. amygdalina leaves extracts on blood glucose of diabetic rats, the results showed that decrease in blood glucose after administration of the extracts may be associated with the presence vitamins, phytochemicals, and other nutrients in the extracts [27,28]. Thus, the presence of trigonelline and caffeoylquinic acid derivative might be attributed to the anti-diabetic activity of the extracts [29,30].…”
mentioning
confidence: 97%